Representation of Ethnic Symbol as an Emergency Status in the Movie “Tunanganku Mautku”: Semiotics Analysis - Wali, Abdul; Ibtisam; Sulistyowati; Firmonasari, Aprillia (BRIN Publishing (Penerbit BRIN), 2024)
A movie that portrays the traditions of its own region is more effective in conveying moral messages based on events that have occurred. Therefore, this research examines the representation of a short movie originating from the Madurese community titled